“The Dogs Saved My Life”: The Role of Prison Dog Programs in the Turning Point Process Among Formerly Incarcerated Men - Wesely, Jennifer K. (The prison journal, 2025)
This article examines the mechanisms underlying “turning point” processes among participants in Prison Dog Programs (PDPs). Despite the coercive and violent elements that characterize prisons, there may still be space for positive transitions. While most opportunities for personal growth in prison are limited, or truncated, PDPs are unique. They demand immersive investment through which strong bonds develop between human and dog. Based on in-depth interviews with formerly incarcerated men, this article examines how the meaningful relationships they built with the dogs while in a PDP facilitated inner change, playing a major role in their turning point processes.